2014
DOI: 10.1007/978-94-017-9343-8_2
|View full text |Cite
|
Sign up to set email alerts
|

Urea

Abstract: Urea is generated by the urea cycle enzymes, which are mainly in the liver but are also ubiquitously expressed at low levels in other tissues. The metabolic process is altered in several conditions such as by diets, hormones, and diseases. Urea is then eliminated through fluids, especially urine. Blood urea nitrogen (BUN) has been utilized to evaluate renal function for decades. New roles for urea in the urinary system, circulation system, respiratory system, digestive system, nervous system, etc., were report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 202 publications
2
21
0
1
Order By: Relevance
“…In fact, end-stage renal diseases are found to play dominant roles in the neoplastic development of renal cell carcinoma; patients, especially those undergoing hemodialysis, are strongly advised to avoid a high-protein diet in order to reduce the urea production that constitutes a nitrogen burden. This is consistent with the fact that urea is an indispensable biomarker in clinical diagnosis and is strongly associated with kidney function [ 19 , 20 ] . Glomerulonephritis, nephritis, and renal failure result in the accumulation of urea in the blood, and excessive urea is harmful to the human liver, kidney, and lung.…”
Section: Introductionsupporting
confidence: 85%
“…In fact, end-stage renal diseases are found to play dominant roles in the neoplastic development of renal cell carcinoma; patients, especially those undergoing hemodialysis, are strongly advised to avoid a high-protein diet in order to reduce the urea production that constitutes a nitrogen burden. This is consistent with the fact that urea is an indispensable biomarker in clinical diagnosis and is strongly associated with kidney function [ 19 , 20 ] . Glomerulonephritis, nephritis, and renal failure result in the accumulation of urea in the blood, and excessive urea is harmful to the human liver, kidney, and lung.…”
Section: Introductionsupporting
confidence: 85%
“…The significant differences with increasing means in urinary concentrations of citrulline, N-methylarginine, methylsuccinate and urea between V1 and V3 within the CG can hardly be explained and might be due to uncontrolled variation. For example, the documented increase in urinary urea levels could likely be an effect of diet—i.e., of an increased protein intake—as urea represents the terminal product of protein catabolism, being eliminated in urine [62].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired insulin secretion and insulin resistance have been observed among chronic kidney disease (CKD) patients, mainly due to the retention of uremic metabolites including urea. Blood urea nitrogen (BUN), as a traditional marker for renal function for decades, recent attention has been given to the new role in urinary system, circulatory system, etc., which suggests clinical significance of urea [4]. Experimental evidence indicated that uremic mice displayed glucose intolerance, while urea infusion in normal animals elevated insulin resistance-associated adipokines [5,6].…”
mentioning
confidence: 98%